The Publishing Industry in Spain: A Perspective Review of Two Decades Transformation - Magadán Díaz, Marta; Rivas García, Jesús Israel (Publishing Research Quarterly, 2021)
The main aim of this study is to examine the leading transformations that have occurred throughout the period 2000-2018 in the Spanish publishing industry as a consequence of technological change and its adaptation to the new digital environment. Firstly, this work focuses on the economic importance of Spanish publishing sector studying three key variables: production, employment, and export capacity; secondly, the analysis moves along the structural changes in the Spanish publishing sector through the new millennium, and thirdly, this study discusses on the main business models emerged in the heat of technological disruption. Finally, conclusions close this research.
Keywords: publishing industry; print-on-demand; digital content; e-book; Spain; Emerging; Scopus